Islamic Religious Education Teachers' Strategies in Improving the Morals of Students in Islamic Boarding Schools - Pasaleron, Roni; Sarianto, Debi; Fahmi, Muhammad Ilham; Syamsudin, Syamsudin (Khalaqa: Journal of Education and Learning, 2024)
Teachers must be creative in preparing media and learning tools to guide students to become intelligent, creative individuals with strong diversity and integrity. This study aims to identify the types, procedures, and influencing factors of learning media that enhance students’ motivation in Fiqh learning at Senior High Schools. Using a qualitative descriptive approach, data were collected through field studies and literature reviews, with analysis conducted via interviews, documentation, and observation. The research was carried out in Senior High Schools. The findings reveal: (1) Types of media used include photos, concept maps, posters, audio recordings, radio, learning videos, textbooks, worksheets, WhatsApp, YouTube, Google, PowerPoint, puppets, and whiteboards; (2) Media usage steps involve preparation, implementation/presentation, and follow-up; (3) Supporting factors include teacher competence, funding, media availability, flexibility, and school support; (4) Inhibiting factors include limited time, inadequate facilities, and unsupportive school environments